Incorporation of dual nanoplatelets to a natural polymer for foldable, robust, bioactive, and biocompatible nacre-like nanocomposites. (1st June 2021) - Wan, Yizao; Zhu, Xiangbo; Huang, Zhihuan; Peng, Mengxia; Luo, Honglin
Abstract: Novel nacre-inspired nanocomposites composed of layered hydroxyapatite (LHAp), graphene oxide (GO), and konjac glucomannan (KGM) were fabricated via evaporation-induced assembly for the first time. The morphology, structure, mechanical properties, biocompatibility, and bioactivity of the LHAp/GO/KGM nanocomposites were studied and the effect of LHAp content was determined. Scanning electron microscopy (SEM) suggests that the formation of brick and mortar (B&M)-like layered structure is dependent on LHAp content. Two-dimensional small-angle X-ray scattering (2D-SAXS) analysis reveals the alignment of LHAp nanosheets in LHAp/GO/KGM nanocomposites. The B&M-like structure endows the LHAp/GO/KGM nanocomposites with excellent mechanical strength. The tensile strength of LHAp/GO/KGM-20 reaches 153.4 MPa, which is approximately 3.1 times higher than that of bare KGM film, exceeds all HAp-based composites reported by far. In addition, the LHAp/GO/KGM nanocomposites with 10 wt% LHAp show excellent biocompatibility and bioactivity. Graphical abstract: Image 1 Highlights: Nacre-like composites of layered hydroxyapatite (LHAp), graphene oxide (GO), and konjac glucomannan (KGM). The LHAp/GO/KGM nanocomposites were prepared via evaporation-induced assembly. The formation of brick & mortar-like structure is controlled by LHAp content. The composite with a suitable LHAp content shows excellent bioactivity and biocompatibility. The tensile strength of LHAp/GO/KGM exceeds previously reported HAp-based composites.